2005
DOI: 10.1016/j.neuron.2004.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Associative Short-Term Synaptic Plasticity Mediated by Endocannabinoids

Abstract: Associative learning is important on rapid timescales, but no suitable form of short-term plasticity has been identified that is both associative and synapse specific. Here, we assess whether endocannabinoids can mediate such plasticity. In the cerebellum, bursts of parallel fiber (PF) activity evoke endocannabinoid release from Purkinje cell dendrites that results in retrograde synaptic inhibition lasting seconds. We find that the powerful climbing fiber (CF) to Purkinje cell synapse regulates this inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
187
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(193 citation statements)
references
References 53 publications
5
187
1
Order By: Relevance
“…Thus, during EBC, endocannabinoids may operate by activating presynaptic CB1 receptors on parallel fiber terminals, which reduce Ca 2 + influx, ultimately inhibiting Purkinje cell activity by decreasing glutamate release from parallel fiber terminals. Indeed, it has recently been shown that concurrent parallel fiber/climbing fiber activation of Purkinje cells (which is analogous to convergent CS-US input) leads to short-term depression of the parallel fiber synapse, an effect which is mediated by endocannabinoids (Brenowitz and Regehr, 2005). Such an effect may be crucial for the induction of longer-lasting synaptic plasticity, such as endocannabinoid-mediated long-term depression (LTD; Safo and Regehr, 2005), which itself may represent the neural substrate of EBC (Thompson and Kim, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during EBC, endocannabinoids may operate by activating presynaptic CB1 receptors on parallel fiber terminals, which reduce Ca 2 + influx, ultimately inhibiting Purkinje cell activity by decreasing glutamate release from parallel fiber terminals. Indeed, it has recently been shown that concurrent parallel fiber/climbing fiber activation of Purkinje cells (which is analogous to convergent CS-US input) leads to short-term depression of the parallel fiber synapse, an effect which is mediated by endocannabinoids (Brenowitz and Regehr, 2005). Such an effect may be crucial for the induction of longer-lasting synaptic plasticity, such as endocannabinoid-mediated long-term depression (LTD; Safo and Regehr, 2005), which itself may represent the neural substrate of EBC (Thompson and Kim, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We also show that mGluR1 activation combined with depolarization leads to the production of an endocannabinoid, 2-arachidonoyl glycerol (2-AG) , which is known to be produced from DG by diacylglycerol lipase (Sugiura et al 2006). Brenowits and Regehr observed that coactivation of parallel and climbing fibres markedly facilitated endocannabinoidmediated suppression of the parallel fibre synapses, presumably owing to the cooperativity of parallel fibreinduced mGluR1 activation and climbing fibreinduced Ca 2C elevation (Brenowitz & Regehr 2005). Thus, endocannabinoid-mediated retrograde suppression, dependent on both mGluR1 and Ca 2C , may constitute a local negative feedback loop to prevent the hyper-excitation of Purkinje cells.…”
Section: Endocannabinoid Signalling (A)mentioning
confidence: 72%
“…Of the five known mAChR subtypes (M1-5), M1, M3, and M5 are G q -coupled receptors linked to the activation of phospholipase C (PLC) β isoforms (31,32). PLCβ is a key element in the cannabinoid synthesis pathway (25) and is also activated by metabotropic glutamate receptor type 1 (mGluR1) (33), the metabotropic glutamate receptor required for synaptically evoked cannabinoid signaling in Purkinje cells (27), raising the possibility that mAChRs and mGluR1 trigger cannabinoid signaling through a common mechanism. To test this possibility, we assessed the effect of oxo-m on PF-LTP with the PLC inhibitor U-73122 (5 ÎźM) present in the bath throughout the recording, and found that the muscarinic agonist did not suppress PF-LTP under these conditions (+22.6 Âą 6.7%; n = 7; t = 31-35min; P = 0.01471) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cannabinoids are released from the postsynaptic cells and bind to cannabinoid 1 receptors (CB1Rs) on presynaptic terminals, where they diminish neurotransmitter release probability through a G i/o -coupled pathway (25). In addition to transiently reducing synaptic strength (26,27), cannabinoid release has been shown to inhibit a presynaptic form of long-term potentiation (LTP) at PF-Purkinje cell synapses (PF-LTP) by suppressing the activation of adenylyl cyclase (28). Here we demonstrate that cholinergic signaling and the activation of mAChRs on Purkinje cells blocks the induction of presynaptic PF-LTP.…”
mentioning
confidence: 99%